1999
DOI: 10.1103/physrevlett.82.3677
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electron Scattering on Second Derivative Ballistic Electron Emission Spectroscopy inAu/GaAs/AlGaAsHeterostructures

Abstract: We present a quantitative study of the second voltage derivative (SD) of ballistic electron emission spectra of Au͞GaAs͞AlGaAs heterostructures to probe the effect of electron scattering on these spectra. Our analysis of the SD spectra shows that strong electron scattering occurs at the nonepitaxial Au͞GaAs interface, leading to an experimentally observed redistribution of current among the electron transport channels. We also show that the effects of hot-electron scattering inside the semiconductor modify the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Although scattering rates may be further surpressed at 4.2 K, the contribution of X electrons is still largely attentuated since their mfp is still much shorter than the combined thickness of the GaAs cap and the barrier layers (∼50 nm). Previous BEEM work on direct-gap GaAs/Al x Ga 1−x As (x≤0.42) SB HJs found that the collector current is composed only of Γ and L electrons [16], and the contribution from the offaxis L channel is greater due to interfacial scatterings at the m-s interface. The main results from the quaternary AlGaInP alloy system are shown in Fig.…”
mentioning
confidence: 93%
“…Although scattering rates may be further surpressed at 4.2 K, the contribution of X electrons is still largely attentuated since their mfp is still much shorter than the combined thickness of the GaAs cap and the barrier layers (∼50 nm). Previous BEEM work on direct-gap GaAs/Al x Ga 1−x As (x≤0.42) SB HJs found that the collector current is composed only of Γ and L electrons [16], and the contribution from the offaxis L channel is greater due to interfacial scatterings at the m-s interface. The main results from the quaternary AlGaInP alloy system are shown in Fig.…”
mentioning
confidence: 93%
“…A heterostructure can be placed in the base itself 7 or in the collector, 8 close to the base-collector interface. Much work in this field has focused on ballistic transport through single barriers, 9 double resonant barriers, 10 quantum dots, 11 and superlattices. [12][13][14] A well-developed theory has been implemented to predict the observed voltage-current relation to the actual transmission function through the structure by making use of the bulk conduction-band offsets and effective masses.…”
Section: Introductionmentioning
confidence: 99%
“…7 The nonepitaxial interface scattering and lateral momentum nonconservation have been verified by ballistic electron emission microscopy for some metal/semiconductor interfaces. 8,9 However, the thermionic emission current enhancement needs to be further quantified for these experiments.…”
mentioning
confidence: 99%